Social media and the prohibition of ‘false news’: can the free speech jurisprudence of the African Commission on Human and Peoples’ Rights provide a litmus test? (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:Based on free speech theories, international human rights law, opinions of human rights mechanisms and scholars, this article argues that the African Commission on Human and Peoples’ Rights (African Commission) should expand its ‘traditional’ free speech jurisprudence to meet the exigencies of adjudicating emergent cybercrime laws in Africa that criminalise ‘fake news’ on social media. While social media’s expansion of opportunities to exercise the right to free speech and power to challenge dominant discourses deepen Africa’s democratisation, its propensity for abuse must nonetheless be addressed. Consequently, many African governments have interfered with internet access either during public protests or election periods and resorted to ill-conceived cybercrime laws that criminalise the communication of so-called ‘fake news’ on social media. Around 23 African states have cybercrime laws in place that contain provisions criminalising ‘fake news’. These states include Botswana, Burkina Faso, the Democratic Republic of Congo, Egypt, Ethiopia, Gabon, Kenya, Malawi, Nigeria, Tanzania, Togo and Uganda. Despite being unduly protective of high-ranking government officials, these criminal libel laws present many conceptual and legal difficulties. Nonetheless, the African Commission can resolve these challenges and effectively tackle disinformation on social media through a creative interpretation of article 9 of the African Charter on Human and Peoples’ Rights. TITRE ET RÉSUMÉ EN FRANCAIS:Interruption d’accès aux réseaux sociaux et interdiction des «fausses informations»: la jurisprudence de la Commission africaine des droits de l’homme et des peuples sur la liberté d’expression peut-elle fournir un test décisif?RÉSUMÉ:En se fondant sur les théories relatives à la liberté d’expression, sur le droit international des droits de l’homme ainsi que sur les opinions des mécanismes des droits de l'homme et la doctrine, le présent article soutient que la Commission africaine des droits de l’homme et des peuples (Commission africaine) devrait étendre sa jurisprudence «traditionnelle» sur la liberté d'expression pour répondre aux exigences du contentieux sur les lois émergentes relatives à la cybercriminalité en Afrique qui criminalisent la publication de «fausses informations» sur les réseaux sociaux. Si l’élargissement des possibilités offertes par les médias sociaux pour exercer le droit à la liberté d’expression et le pouvoir de contester les discours dominants est une valeur ajoutée à la démocratisation en Afrique, sa propension aux abus doit néanmoins être abordée. Par conséquent, de nombreux gouvernements africains ont interféré avec l’accès à internet pendant les manifestations publiques ou les périodes électorales et ont recouru à des lois mal conçues sur la cybercriminalité qui criminalisent la communication des fameuses «fake news» sur les réseaux sociaux. Cette question concerne plus de la moitié des 23 lois africaines sur la cybercriminalité, notamment celles du Kenya, de l'Éthiopie, du Malawi, du Nigéria, de la Tanzanie, de l'Ouganda, de l'Égypte, de la Rd Congo, du Gabon, du Togo, du Botswana et du Burkina Faso. Bien qu'elles protègent indûment les hauts fonctionnaires du gouvernement, ces lois sur la diffamation comme délit présentent de nombreuses difficultés conceptuelles et juridiques. Néanmoins, la Commission africaine peut résoudre ces défis et lutter efficacement contre la désinformation sur les réseaux sociaux grâce à une interprétation innovante de l’article 9 de la Charte africaine des droits de l’homme et des peuples.